2014
DOI: 10.1016/j.rboe.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the results from simple radiography, from before to after Salter osteotomy, in patients with Legg-Calvé-Perthes disease

Abstract: ObjectivesTo determine whether the clinical variables and preoperative classification of patients with Legg-Calvé-Perthes disease (LCPD) who undergo Salter osteotomy correlate with the radiographic result at the time of skeletal maturity.MethodsIn this retrospective cohort study, 47 individuals with LCPD who were treated using Salter osteotomy (1984–2004) were evaluated. The patients were evaluated according to sex, skin color, side affected and age at which osteotomy was performed. The preoperative radiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…The classification of Laredo (30) ( Table 5) has a high prognostic value (31). Nevertheless, its difficulties of realization make it little usable in clinical routine.…”
Section: Arthrographymentioning
confidence: 99%
“…The classification of Laredo (30) ( Table 5) has a high prognostic value (31). Nevertheless, its difficulties of realization make it little usable in clinical routine.…”
Section: Arthrographymentioning
confidence: 99%
“…İyi sonuçların genellikle 6-8 yaş arasında Lateral Pillar sınıflamasına göre Tip B ve B/C kalçalarla ilgili olduğu, Tip C tipi kalçalarda ise sonuç-ların daha kötü olduğu vurgulanmıştır. [14,46] Herring ve arkadaşları [47] , farklı tedavi yöntemlerini karşılaştırdıkları çok merkezli ileriye dönük çalışmada, başlangıç yaşları 6-8 yıl arasında olan olgularda en başarılı sonuçları Salter osteotomisiyle tedavi ettikleri grupta bulmuşlardır (%69 Stulberg Tip I ve II).…”
Section: İnnominat Osteotomiunclassified
“…It is the main form of hip disease in children, with an incidence rate of 2-294 per 1,000,000 children [2]. Despite the many studies that have been conducted, the etiology and optimal treatment remain unclear [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have indicated that the classification of LCPD corresponds to the disease stage, outcome, and predictors of outcome [3]. Understanding the disease's pathophysiology helps identify four progression stages through radiography, including initiation, fragmentation, re-ossification, and healing [4]. Outcomes have also been classified radiographically based on the femoral head shape and joint congruency [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation